Efektivitas Penggunaan Aplikasi Quizizz dalam Melakukan Assesment Diagnostik Non Kognitif Siswa Kelas 12 IPS Lintas Minat di SMA YPHB Kota Bogor - Suci Mustika Hati (Arus Jurnal Pendidikan, 2021)
The condition of the covid-19 pandemic that requires students to study at home on an online basis. Teachers and students directly change the learning process that is usually done in the classroom into distance learning. This makes teachers forget to consider the readiness of students non-cognitively during online learning. Therefore, the government issued an emergency curriculum during the pandemic. In addition, the Ministry of Education and Culture also urges all teachers to carry out non-cognitive diagnostic assessments on a regular basis in order to determine the readiness of students both emotionally and psychologically in accepting online learning. To carry out the diagnostic assessment, there are many special platforms that can be used to assist teachers in carrying out non-cognitive diagnostic assessments, one of which is using the quizziz platform. The results of this observation can determine the effectiveness of the quizziz platform in the implementation of non-cognitive diagnostic assessments.